Are social enterprises technological innovative? A quantitative analysis on social entrepreneurs in emerging countries - Del Giudice, Manlio; Garcia-Perez, Alexeis; Scuotto, Veronica; Orlando, Beatrice (Technological Forecasting and Social Change, 2019)
Technological innovation is the new backbone for companies. Exploiting and exploring new knowledge increase the chance of survival in the current dynamic market. Alongside, there are countries were be an innovative need to face up social and political challenges. This has transformed their economy, spreading an entrepreneurial mindset mingled with the willing to help a local community. This phenomenon is called social entrepreneurship which is leveraging new economies and building wealth, environmental system. In this vein, the present research seeks to offer qualitative research on 142 social entrepreneurs in an emerging country. The scope is to analyse if social entrepreneurship, entrepreneurial characteristics, and entrepreneurial ecosystem influence innovation. As emerged, technological innovation is affected by the first two factors but the entrepreneurial ecosystem is still not supportive. New, several activities should be organised by the government to assist entrepreneurs, whereas, the entrepreneurs are socially motivated to build up his enterprise.
Keywords: Analyse quantitative; Réservé UdeM